Conductive agent and preparation method thereof, pole piece, secondary battery and electric device

By using nitrogen-doped porous carbon nanosheets as conductive agents, the problems of insufficient conductivity and high cost of existing conductive agents are solved, and the battery cycle performance is improved and the cost is reduced, which is suitable for large-scale industrial applications.

CN119650700APending Publication Date: 2025-03-18REPT BATTERO ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411844455.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The conductivity of existing secondary batteries is insufficient, which affects the cycling performance of the battery. At the same time, the cost of graphene conductive agent is high and is not suitable for large-scale industrial applications.

Method used

Nitrogen-doped porous carbon nanosheets with a sheet-layer structure are used as conductive agents, and the nitrogen source and zinc salt are doped to the carbon nanosheets through hydrothermal reactions to form a porous structure, improving conductive properties and reducing costs.

Benefits of technology

It improves the conductive properties of the conductive agent, enhances the circulation performance of the battery, and reduces the material cost of the conductive agent, making it suitable for large-scale industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650700A_ABST
    Figure CN119650700A_ABST
Patent Text Reader

Abstract

The invention relates to a conductive agent and a preparation method thereof, a pole piece, a secondary battery and an electric device. The conductive agent comprises a nitrogen-doped porous carbon nanosheet with a lamellar structure. According to the conductive agent provided by the invention, the nitrogen-doped porous carbon nanosheet with the lamellar structure is adopted as the conductive agent, on one hand, the lamellar structure forms a large-area conductive network, so that electrons can be conducted in a two-dimensional space, and meanwhile, nitrogen is doped in the carbon nanosheet to introduce additional conductive contact sites; the porous structure effectively increases the specific surface area, so that the conductivity of the conductive agent is improved. And on the other hand, the material cost of the conductive agent is reduced, and through the synergistic effect of nitrogen doping and the porous structure, the dispersity of the conductive agent in the slurry is improved, the agglomeration phenomenon is reduced, the preparation yield of the pole piece is improved, and large-scale industrial application is further facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a conductive agent and a preparation method thereof, a pole piece, a secondary battery, and an electrical device. Background Art

[0002] With the increasing demand for clean energy and the rapid development of the new energy field, secondary batteries as energy sources are widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields, which puts higher requirements on the conductivity of the conductive agent of secondary batteries.

[0003] In traditional technology, point-type conductive agents such as carbon black are usually used. The conductivity of such conductive agents is average. When applied to the electrode, it affects the cycle performance of the battery. Therefore, graphene has emerged as a conductive agent. Graphene has advantages in building the electrode conductive network with its "point-surface" contact mode, and has better conductivity, larger specific surface area, and stronger liquid absorption capacity than traditional conductive carbon materials.

[0004] However, graphene materials are expensive, which is not conducive to large-scale industrial applications. Summary of the invention

[0005] Based on this, it is necessary to provide a conductive agent and its preparation method, electrode, secondary battery, and electrical device to improve the conductivity of the conductive agent, thereby improving the cycle performance of the battery and reducing the material cost of the conductive agent, which is conducive to large-scale industrial applications.

[0006] A first aspect of the present application provides a conductive agent, which includes: nitrogen-doped porous carbon nanosheets having a sheet structure.

[0007] In some embodiments, the pores of the nitrogen-doped porous carbon nanosheets include one or more of spherical pores and cylindrical pores.

[0008] In some embodiments, the average thickness of a single layer of the nitrogen-doped porous carbon nanosheet is 5 nm to 50 nm.

[0009] In some embodiments, the specific surface area of ​​the nitrogen-doped porous carbon nanosheet is 100 m 2 / g~150m 2 / g.

[0010] In some embodiments, the porosity of the nitrogen-doped porous carbon nanosheets is 70% to 85%.

[0011] In some embodiments, the single-layer electrical conductivity of the nitrogen-doped porous carbon nanosheets is 90 S / cm to 110 S / cm.

[0012] The second aspect of the present application provides a method for preparing a conductive agent, which comprises the following steps: adding carbon nanosheets, a nitrogen source and a zinc salt into a solvent for a hydrothermal reaction, centrifugally drying and calcining after the reaction, and acid washing after cooling to obtain a conductive agent; wherein the conductive agent comprises nitrogen-doped porous carbon nanosheets, and the nitrogen-doped porous carbon nanosheets have a lamellar structure.

[0013] In some embodiments, the maximum value of the calcination temperature is ≥ 1000°C.

[0014] In some embodiments, the mass ratio of carbon nanosheets to zinc salt is 1:(4-8).

[0015] The third aspect of the present application provides a pole piece, which includes: a current collector; and an active material layer, which is arranged on at least a portion of the surface of the current collector, and the active material layer includes an active material and a conductive agent, and the conductive agent includes the conductive agent provided in the first aspect above or the conductive agent prepared by the preparation method provided in the second aspect above.

[0016] In some embodiments, the mass percentage of the conductive agent in the active material layer is 0.6% to 1%.

[0017] A third aspect of the present application provides a secondary battery, which includes the electrode provided by the second aspect.

[0018] A fourth aspect of the present application provides an electrical device, which includes the secondary battery provided by the third aspect.

[0019] Compared with the traditional technology, this application has at least the following beneficial effects:

[0020] The conductive agent provided in the present application adopts nitrogen-doped porous carbon nanosheets with a lamellar structure as the conductive agent. On the one hand, the lamellar structure forms a large-area conductive network, providing a large number of conductive contact sites for the active material particles of the electrode, so that electrons can be conducted in a two-dimensional space. The porous structure effectively increases the specific surface area. At the same time, nitrogen doping introduces additional conductive contact sites in the carbon nanosheets, changes the surface chemical state of the carbon carrier, enhances the surface affinity of the carbon material, and further enhances the interaction with lithium ions, thereby improving the conductive properties of the conductive agent and further improving the cycle performance of the battery.

[0021] On the other hand, compared with traditional graphene conductive agents, nitrogen-doped porous carbon nanosheets have lower costs, and through the synergistic effect of nitrogen doping and porous structure, the doping of nitrogen atoms increases the surface polarity of the carbon nanosheets, thereby reducing the interaction between the sheets; the porous structure is distributed in the sheet structure, so that a certain spatial barrier effect is produced between the sheets, reducing the interaction between the sheets, and at the same time, the porous structure can also increase the wettability of the solvent, thereby improving the dispersion of the conductive agent in the slurry, reducing the occurrence of agglomeration, and improving the preparation yield of the electrode, which is beneficial to large-scale industrial applications.

[0022] In summary, the conductive agent provided in the present application improves the conductive properties of the conductive agent, thereby improving the cycle performance of the battery, while reducing the material cost of the conductive agent and improving the dispersibility of the conductive agent in the electrode slurry, which is conducive to large-scale industrial applications.

[0023] The above is only a possible speculation on the mechanism of the present application and does not constitute a limitation on the scope of protection of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a SEM test image of the conductive agent in ethanol in Example 1 of the present application.

[0025] Figure 2 This is a TEM test image of the conductive agent in ethanol in Example 1 of the present application. DETAILED DESCRIPTION

[0026] References to embodiments of the present application will now be provided in detail, one or more examples of which are described below. Each example is provided as an explanation rather than a limitation of the present application. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present application without departing from the scope or spirit of the present application. For example, a feature described or described as part of one embodiment may be used in another embodiment to produce a further embodiment.

[0027] Therefore, it is intended that the present application covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present application are disclosed in or are apparent from the following detailed description. It will be appreciated by those of ordinary skill in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the present application.

[0028] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0029] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0030] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0031] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0032] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, it is mentioned that the method may also include step (c), which means that step (c) can be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0033] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0034] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0035] A first aspect of the present application provides a conductive agent, which includes nitrogen-doped porous carbon nanosheets, and the nitrogen-doped porous carbon nanosheets have a sheet structure.

[0036] The conductive agent provided in the present application adopts nitrogen-doped porous carbon nanosheets with a lamellar structure as the conductive agent. On the one hand, the lamellar structure forms a large-area conductive network, providing a large number of conductive contact sites for the active material particles of the electrode, so that electrons can be conducted in a two-dimensional space. The porous structure effectively increases the specific surface area. At the same time, nitrogen doping introduces additional conductive contact sites in the carbon nanosheets, changes the surface chemical state of the carbon carrier, enhances the surface affinity of the carbon material, and further enhances the interaction with lithium ions, thereby improving the conductive properties of the conductive agent and further improving the cycle performance of the battery.

[0037] On the other hand, compared with traditional graphene conductive agents, nitrogen-doped porous carbon nanosheets have lower costs, and through the synergistic effect of nitrogen doping and porous structure, the doping of nitrogen atoms increases the surface polarity of the carbon nanosheets, thereby reducing the interaction between the sheets; the porous structure is distributed in the sheet structure, so that a certain spatial barrier effect is produced between the sheets, reducing the interaction between the sheets, and at the same time, the porous structure can also increase the wettability of the solvent, thereby improving the dispersion of the conductive agent in the slurry, reducing the occurrence of agglomeration, and improving the preparation yield of the electrode, which is beneficial to large-scale industrial applications.

[0038] In summary, the conductive agent provided in the present application improves the conductive properties of the conductive agent, thereby improving the cycle performance of the battery, while reducing the material cost of the conductive agent and improving the dispersibility of the conductive agent in the electrode slurry, which is conducive to large-scale industrial applications.

[0039] The above is only a possible speculation on the mechanism of the present application and does not constitute a limitation on the scope of protection of the present application.

[0040] In some embodiments, the pores of the nitrogen-doped porous carbon nanosheets include one or more of spherical pores and cylindrical pores.

[0041] The spherical pores and cylindrical pores increase the specific surface area of ​​the conductive agent, provide more conductive contact sites, and further improve the conductive performance of the conductive agent. The shape design of the spherical pores and cylindrical pores further strengthens the isolation between the layer structures and reduces the interaction between the layers. At the same time, the porous structure can also increase the wettability of the solvent, thereby improving the dispersion of the conductive agent in the slurry, reducing the occurrence of agglomeration, and improving the preparation yield of the electrode, which is beneficial to large-scale industrial applications.

[0042] The present application does not limit the formation method of the spherical pores and cylindrical pores on the nitrogen-doped porous carbon nanosheets.

[0043] In some embodiments, the spherical pores and the cylindrical pores are obtained by mixing the carbon nanosheets with the nitrogen source and the zinc salt by hydrothermal reaction, sintering and acid washing. It is understood that the carbon nanosheets, the nitrogen source and the zinc salt undergo hydrothermal reaction, the nitrogen element and the zinc salt are doped into the carbon nanosheets, and the zinc salt is converted into rod-shaped ZnO molecules or spherical Zn atoms after sintering, and finally after high-temperature volatilization and acid washing, the nitrogen-doped carbon nanosheets form corresponding cylindrical pores or spherical pores.

[0044] In some embodiments, the average thickness of a single layer of nitrogen-doped porous carbon nanosheets is 5 nm to 50 nm. Exemplarily, the average thickness of a single layer of nitrogen-doped porous carbon nanosheets may be, but is not limited to, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm. Further, the average thickness of a single layer of nitrogen-doped porous carbon nanosheets is 10 nm to 20 nm.

[0045] Herein, the “average thickness of a single layer” refers to the arithmetic mean of the thicknesses of 10 randomly selected single layers.

[0046] In some embodiments, the nitrogen-doped porous carbon nanosheet has a specific surface area of ​​100 m 2 / g~150m 2 / g. For example, the specific surface area of ​​the nitrogen-doped porous carbon nanosheets may be, but is not limited to, 100 m 2 / g, 110m 2 / g, 120m 2 / g, 130m 2 / g, 140m 2 / g, 150m 2 / g. Furthermore, the specific surface area of ​​nitrogen-doped porous carbon nanosheets is 110 m 2 / g~120m 2 / g.

[0047] As used herein, "specific surface area" refers to the total area per unit mass of a material.

[0048] In some embodiments, the porosity of the nitrogen-doped porous carbon nanosheet is 70% to 85%. For example, the porosity of the nitrogen-doped porous carbon nanosheet can be, but is not limited to, 70%, 75%, 80%, or 85%.

[0049] Herein, "porosity" refers to the ratio of the pore volume in the nitrogen-doped porous carbon nanosheet to the total volume of the porous carbon nanosheet.

[0050] In some embodiments, the average pore size of the nitrogen-doped porous carbon nanosheet is 5nm to 50nm. Exemplarily, the average pore size of the nitrogen-doped porous carbon nanosheet can be, but is not limited to, 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm. Further, the average pore size of the nitrogen-doped porous carbon nanosheet is 10nm to 20nm.

[0051] Herein, “average pore size” refers to the statistical average of the sizes of all pores in the nitrogen-doped porous carbon nanosheets.

[0052] In some embodiments, the single-layer conductivity of the nitrogen-doped porous carbon nanosheet is 90S / cm to 110S / cm. Exemplarily, the single-layer conductivity of the nitrogen-doped porous carbon nanosheet may be, but is not limited to, 90S / cm, 95S / cm, 100S / cm, 105S / cm, 110S / cm. Further, the single-layer conductivity of the nitrogen-doped porous carbon nanosheet is 100S / cm to 110S / cm.

[0053] Herein, “single-layer conductivity” refers to the average conductivity of the nitrogen-doped porous carbon nanosheets having a multi-layer structure averaged over each layer.

[0054] The second aspect of the present application provides a method for preparing a conductive agent, which comprises the following steps: adding carbon nanosheets, a nitrogen source and a zinc salt into a solvent for a hydrothermal reaction, centrifugally drying and calcining after the reaction, and acid washing after cooling to obtain a conductive agent.

[0055] The conductive agent includes nitrogen-doped porous carbon nanosheets, and the nitrogen-doped porous carbon nanosheets have a layered structure.

[0056] The preparation method of the conductive agent provided in the present application is to dope the nitrogen source and zinc salt into the carbon nanosheet by hydrothermal reaction, and then calcine to decompose and volatilize the zinc salt, thereby forming a porous structure on the surface of the nitrogen-doped carbon nanosheet, increasing the specific surface area of ​​the conductive agent, effectively increasing the contact sites for electronic conduction, and forming a stable conductive network. The doping of nitrogen atoms and the porous structure work synergistically to reduce the interaction between the sheets, increase the wettability of the solvent, make the conductive agent more dispersible in the slurry, reduce the occurrence of agglomeration, and improve the preparation yield of the pole piece, which is conducive to large-scale industrial application. After pickling, the zinc element is completely removed, so that the conductive agent does not have active sites for electrochemical reactions, which meets the stability and inactivity requirements of the conductive agent.

[0057] In addition, the preparation method of the conductive agent in the present application is simple, highly operable, and has a low preparation cost, which is conducive to large-scale industrial application.

[0058] In some embodiments, the mass ratio of carbon nanosheets to zinc salt is 1:(4-8). For example, the mass ratio of carbon nanosheets to zinc salt can be, but is not limited to, 1:4, 1:5, 1:6, 1:7, 1:8.

[0059] In some embodiments, the nitrogen source is selected from one or more of D-(+)-glucosamine hydrochloride, melamine, and dicyandiamide. Further, the nitrogen source is D-(+)-glucosamine hydrochloride. Thus, it can provide a nitrogen source and can also be combined with the carbon nanosheet as a part of the carbon source.

[0060] In some embodiments, the zinc salt is selected from one or more of zinc nitrate, zinc chloride and zinc carbonate. Further, the zinc salt is zinc nitrate. When the zinc salt is zinc nitrate, it can be used as a pore-forming agent and can also provide a certain nitrogen source for the nitrogen-doped carbon nanosheets. At the same time, the zinc in the zinc nitrate is easily removed, which meets the stability and inactivity requirements of the conductive agent.

[0061] In some embodiments, the temperature of the hydrothermal reaction is 110° C. to 150° C., and the time of the hydrothermal reaction is 22 hours to 26 hours. Thus, the carbon nanosheets and the zinc salt are fully mixed, so that the specific surface area and conductivity of the carbon nanosheets are further improved, thereby improving the cycle performance of the battery.

[0062] In some of the embodiments, the maximum value of the calcination temperature is ≥1000°C; by controlling the maximum value of the calcination temperature to be ≥1000°C, the zinc element is fully volatilized, the pore-forming effect of the nitrogen-doped carbon nanosheets is ensured, and the specific surface area of ​​the conductive agent is increased.

[0063] It is understood that when the calcination is carried out in a step-by-step temperature increasing manner, the "maximum calcination temperature" herein refers to the temperature used in the last stage of calcination.

[0064] Furthermore, the calcination includes a primary calcination and a secondary calcination performed sequentially, wherein the primary calcination temperature is 400°C to 500°C and the primary calcination time is 2h to 4h; the secondary calcination temperature is 1000°C to 1200°C and the secondary calcination time is 2h to 4h.

[0065] In some embodiments, the acid wash employs 1M H2SO4.

[0066] In some embodiments, the carbon nanosheets are prepared by heating a citrate precursor in an inert atmosphere, grinding it once after cooling, washing it with acid, filtering it, drying it, and finally grinding it twice to obtain the carbon nanosheets.

[0067] In some embodiments, the heating temperature is 700° C. to 900° C., and the heating time is 2 h to 4 h.

[0068] In some implementations, the grinding time is 10min to 20min.

[0069] In some embodiments, the secondary grinding step specifically includes: manually grinding in a clockwise direction for 30 to 45 minutes using an agate mortar. Thus, through the secondary grinding treatment, the prepared carbon nanosheets have a smaller particle size and a larger specific surface area.

[0070] In some embodiments, the drying step specifically includes: vacuum drying at a temperature of 60° C. to 80° C. for 10 h to 15 h.

[0071] The third aspect of the present application provides a pole piece, which includes a current collector and an active material layer. The active material layer is disposed on at least a portion of the surface of the current collector, and the active material layer includes an active material and a conductive agent, and the conductive agent includes the conductive agent provided in the first aspect or the conductive agent prepared by the preparation method provided in the second aspect.

[0072] In some embodiments, the mass percentage of the conductive agent in the active material layer is 0.6% to 1%. For example, the mass percentage of the conductive agent in the active material layer may be, but is not limited to, 0.6%, 0.7%, 0.8%, 0.9%, or 1%. Further, the mass percentage of the conductive agent in the active material layer is 0.8% to 1%.

[0073] In some embodiments, the electrode sheet may be one or more of a positive electrode sheet and a negative electrode sheet.

[0074] Positive electrode:

[0075] The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer. The positive electrode active material layer is arranged on at least a part of the surface of the positive electrode current collector. The positive electrode active material layer comprises a positive electrode active material and the above-mentioned conductive agent.

[0076] As an example, the positive electrode current collector has two surfaces facing each other in its thickness direction, and the positive electrode active material layer is disposed on any one or both of the two facing surfaces of the positive electrode current collector.

[0077] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material on a polymer material substrate. Among them, the metal material includes but is not limited to aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc. Polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0078] In some embodiments, the positive electrode active material may include a positive electrode active material for a battery known in the art.

[0079] As an example, the positive electrode active material of a lithium-ion secondary battery may include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiCoO2), lithium manganese oxide (such as LiCoO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 CO 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.8 Co 0.15 Al 0.05O2) and its modified compounds, etc. Examples of lithium phosphates containing olivine structures may include, but are not limited to, lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), composite materials of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), composite materials of lithium manganese phosphate and carbon, lithium iron manganese phosphate, lithium iron manganese phosphate (LiMn 0.6 Fe 0.4 The weight ratio of the positive electrode active material in the positive electrode active material layer is 80wt% to 100wt%, based on the total weight of the positive electrode active material layer.

[0080] In some embodiments, the positive electrode active material layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylic resin. The weight ratio of the binder in the positive electrode active material layer is 0.01wt% to 20wt%, based on the total weight of the positive electrode active material layer.

[0081] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry, wherein the positive electrode slurry has a solid content of 40wt% to 80wt%, and the viscosity at room temperature is adjusted to 5000mPa·s to 25000mPa·s, the positive electrode slurry is coated on the surface of the positive electrode collector, and after drying, the positive electrode sheet is formed by cold rolling; the positive electrode powder coating unit surface density is 150mg / m 2 ~450 mg / m 2 The compaction density of the positive electrode is 2.0g / cm 3 ~3.6g / cm 3 , optional 2.3g / cm 3 ~3.5g / cm 3 The calculation formula of compaction density is: compaction density = coating surface density / (thickness of the electrode sheet after rolling-thickness of the current collector).

[0082] Negative plate:

[0083] The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer. The negative electrode active material layer is arranged on at least a part of the surface of the negative electrode current collector. The negative electrode active material layer comprises a negative electrode active material and the above-mentioned conductive agent.

[0084] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0085] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material on a polymer material substrate. Among them, the metal material includes but is not limited to copper, copper alloy, nickel, nickel alloy, lithium, lithium alloy, silver and silver alloy, etc. Polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0086] In some of the embodiments, the negative electrode active material of the lithium ion secondary battery may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. The weight ratio of the negative electrode active material in the negative electrode active material layer is 70wt% to 100wt%, based on the total weight of the negative electrode active material layer.

[0087] In some embodiments, the negative electrode active material layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS). The weight ratio of the binder in the negative electrode active material layer is 0.01 wt% to 30 wt%, based on the total weight of the negative electrode active material layer.

[0088] In some embodiments, the negative electrode active material layer may further include other conductive agents. The other conductive agents may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. The weight ratio of the other conductive agents in the negative electrode active material layer is 0.01 wt% to 20 wt%, based on the total weight of the negative electrode active material layer.

[0089] In some embodiments, the negative electrode active material layer may further include other additives, such as a thickener (such as sodium carboxymethyl cellulose (CMC-Na)), etc. The weight ratio of other additives in the negative electrode active material layer is 0.01% to 15wt%, based on the total weight of the negative electrode active material layer.

[0090] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry, wherein the solid content of the negative electrode slurry is 30wt% to 70wt%, and the viscosity at room temperature is adjusted to 2000mPa·s to 10000mPa·s; the obtained negative electrode slurry is coated on the negative electrode collector, and after a drying process, cold pressing such as rolling, a negative electrode sheet is obtained. The negative electrode powder coating unit surface density is 75mg / m 2 ~220 mg / m 2 The compaction density of the negative electrode is 0.5g / m 3 ~2.0g / m 3 .

[0091] A third aspect of the present application provides a secondary battery, which includes the electrode provided by the second aspect.

[0092] Generally, a secondary battery includes a positive electrode, a negative electrode, an electrolyte and a separator. During the charge and discharge process of the battery, active ions are embedded and removed back and forth between the positive electrode and the negative electrode. The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The separator is set between the positive electrode and the negative electrode, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0093] Electrolytes:

[0094] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0095] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0096] In some of the embodiments, the electrolyte salt of the lithium ion secondary battery can be selected from one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0097] In some embodiments, the solvent can be selected from one or more of fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE).

[0098] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0099] Diaphragm:

[0100] In some embodiments, the secondary battery further comprises a separator. The present application has no particular limitation on the type of separator, and any known porous structure separator with good chemical stability and mechanical stability can be selected.

[0101] In some embodiments, the material of the diaphragm can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The diaphragm can be a single-layer film or a multi-layer composite film, without particular limitation. When the diaphragm is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0102] In some embodiments, the positive electrode sheet, the negative electrode sheet and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0103] A fourth aspect of the present application provides an electrical device, which includes the secondary battery provided by the third aspect.

[0104] Secondary batteries can be used as power sources for electrical devices or as energy storage units for electrical devices. Electrical devices may include, but are not limited to, mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. Among them, mobile devices may be, for example, mobile phones, laptops, etc.; electric vehicles may be, for example, pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc., but are not limited to these.

[0105] The present application will be further described below with reference to specific embodiments and comparative examples.

[0106] Example 1

[0107] Conductive agent:

[0108] (1) Weigh 20 g of trisodium citrate dihydrate and place it in a tube furnace. Heat the mixture at 5 °C / min with argon flowing throughout the process. -1 The sample was heated at 800 °C for 3 h at a heating rate, ground once for 10 min after cooling, pickled with 1 M H2SO4, washed with ethanol and deionized water in a filtration device, and vacuum dried at 60 °C for 12 h. Finally, the sample was manually ground clockwise for 45 min using an agate mortar to obtain carbon nanosheets.

[0109] (2) 0.5 g of carbon nanosheets, 1.5 g of D-(+)-glucosamine hydrochloride and 2.23 g of zinc nitrate were stirred in 150 mL of deionized water for 1 h, then reacted in a water bath at 120 °C for 24 h and centrifuged to dry. The resulting solid mixture was placed in a porcelain boat and heated at 5 °C min under Ar gas protection. -1 The heating rate was raised to 400 °C for calcination for 2 h, and then 5 °C·min -1 The temperature was raised to 1100°C for secondary calcination for 2 hours, and then naturally cooled and stirred for 10 minutes at room temperature at a stirring speed of 300 r / min. It was pickled with 1M H2SO4, and then washed with ethanol and deionized water in a suction filtration equipment and then vacuum dried at 60°C for 12 hours to obtain nitrogen-doped porous carbon nanosheets with a lamellar structure, which is the conductive agent.

[0110] Among them, the mass ratio of carbon nanosheets to zinc salt is 1:4.46, and the maximum calcination temperature is 1100°C.

[0111] The conductive agent provided in this embodiment was added to ethanol for SEM and TEM tests. The test results are as follows: Figure 1 and Figure 2 As shown. Figure 1 and Figure 2 The test results show that the conductive agent provided in this embodiment has good dispersibility in the solvent and is not prone to agglomeration. In addition, the dispersibility of nitrogen-doped porous carbon nanosheets in other solvents used for electrode slurry, such as N-methylpyrrolidone and deionized water, is similar to that in ethanol, and is not prone to agglomeration.

[0112] Positive electrode:

[0113] The positive electrode active material lithium iron phosphate (LiFePO4), the binder polyvinylidene fluoride (PVDF) and the conductive agent carbon black (SP) are mixed in a mass ratio of 97.2:2:0.8, and N-methylpyrrolidone is added to prepare a positive electrode slurry; the positive electrode slurry is evenly coated on an aluminum foil, dried, cold pressed, and cut to obtain a positive electrode sheet.

[0114] Negative plate:

[0115] The negative electrode active material artificial graphite, the adhesive styrene butadiene rubber (SBR), the auxiliary agent carboxymethyl cellulose (CMC) and the above-mentioned conductive agent nitrogen-doped porous carbon nanosheets are mixed in a mass ratio of 96.5:1.5:1.2:0.8, and deionized water is added to prepare a negative electrode slurry; the negative electrode slurry is evenly coated on a copper foil, and after drying, it is cold pressed and cut to obtain a negative electrode sheet.

[0116] Diaphragm:

[0117] The polyethylene (PE) separator is 9 μm thick and PVDF with a thickness of 1 μm is dot-coated on both sides.

[0118] Electrolyte:

[0119] 10 wt % of lithium hexafluorophosphate (LiPF6), 1 wt % of vinylene carbonate and 2 wt % of vinyl sulfate (DTD) were added as lithium salt and additives to a mixed solvent of ethylene carbonate (EC): ethyl methyl carbonate (EMC): diethyl carbonate (DEC) = 3:5:2 (mass ratio) to prepare an electrolyte.

[0120] Secondary battery:

[0121] The positive electrode sheet, separator and negative electrode sheet are stacked in order, and then wound into a square bare battery cell, filled with aluminum-plastic film, injected with electrolyte and sealed. After static formation, capacity division and other processes, a secondary battery is obtained.

[0122] Example 2

[0123] The conductive agent, positive electrode sheet, negative electrode sheet, separator, electrolyte and secondary battery provided in this embodiment are basically the same as those in embodiment 1, except that:

[0124] Conductive agent:

[0125] In step (2), the mass of zinc nitrate is 2 g, that is, the mass ratio of carbon nanosheets to zinc salt is 1:4.

[0126] Example 3

[0127] The conductive agent, positive electrode sheet, negative electrode sheet, separator, electrolyte and secondary battery provided in this embodiment are basically the same as those in embodiment 1, except that:

[0128] Conductive agent:

[0129] In step (2), the mass of zinc nitrate is 4 g, and the mass ratio of carbon nanosheets to zinc salt is 1:8.

[0130] Example 4

[0131] The conductive agent, positive electrode sheet, negative electrode sheet, separator, electrolyte and secondary battery provided in this embodiment are basically the same as those in embodiment 1, except that:

[0132] Conductive agent:

[0133] In step (2), the zinc salt is replaced by zinc chloride.

[0134] Example 5

[0135] The conductive agent, positive electrode sheet, negative electrode sheet, separator, electrolyte and secondary battery provided in this embodiment are basically the same as those in embodiment 1, except that:

[0136] Conductive agent:

[0137] In step (2), the temperature of the secondary calcination is 1000°C, that is, the maximum value of the calcination temperature is 1000°C.

[0138] Example 6

[0139] The conductive agent, positive electrode sheet, negative electrode sheet, separator, electrolyte and secondary battery provided in this embodiment are basically the same as those in embodiment 1, except that:

[0140] Conductive agent:

[0141] In step (2), the temperature of the secondary calcination is 950°C, that is, the maximum value of the calcination temperature is 950°C.

[0142] Example 7

[0143] The conductive agent, positive electrode sheet, negative electrode sheet, separator, electrolyte and secondary battery provided in this embodiment are basically the same as those in embodiment 1, except that:

[0144] Positive electrode:

[0145] The positive electrode active material lithium iron phosphate (LiFePO4), the binder polyvinylidene fluoride (PVDF) and the conductive agent nitrogen-doped porous carbon nanosheets are mixed in a mass ratio of 97.2:2:0.8, and N-methylpyrrolidone is added to prepare a positive electrode slurry; the positive electrode slurry is evenly coated on an aluminum foil, dried, cold pressed, and cut to obtain a positive electrode sheet.

[0146] Negative plate:

[0147] The negative electrode active material artificial graphite, the adhesive styrene butadiene rubber (SBR), the auxiliary agent carboxymethyl cellulose (CMC) and the conductive agent carbon black are mixed in a mass ratio of 96.5:1.5:1.2:0.8, and deionized water is added to prepare a negative electrode slurry; the negative electrode slurry is evenly coated on a copper foil, and after drying, it is cold pressed and cut to obtain a negative electrode sheet.

[0148] Example 8

[0149] The conductive agent, positive electrode sheet, negative electrode sheet, separator, electrolyte and secondary battery provided in this embodiment are basically the same as those in embodiment 1, except that:

[0150] In the negative electrode sheet: the negative electrode active material artificial graphite, the adhesive styrene butadiene rubber (SBR), the auxiliary agent carboxymethyl cellulose (CMC) and the above-mentioned conductive agent nitrogen-doped porous carbon nanosheet are mixed in a mass ratio of 96.7:1.5:1.2:0.6.

[0151] Example 9

[0152] The conductive agent, positive electrode sheet, negative electrode sheet, separator, electrolyte and secondary battery provided in this embodiment are basically the same as those in embodiment 1, except that:

[0153] In the negative electrode sheet: the negative electrode active material artificial graphite, the adhesive styrene butadiene rubber (SBR), the auxiliary agent carboxymethyl cellulose (CMC) and the above-mentioned conductive agent nitrogen-doped porous carbon nanosheet are mixed in a mass ratio of 96.3:1.5:1.2:1.

[0154] Comparative Example 1

[0155] The conductive agent, positive electrode sheet, negative electrode sheet, separator, electrolyte and secondary battery provided in this comparative example are basically the same as those in Example 1, except that:

[0156] In step (2), no nitrogen source is added.

[0157] Comparative Example 2

[0158] The conductive agent, positive electrode sheet, negative electrode sheet, separator, electrolyte and secondary battery provided in this comparative example are basically the same as those in Example 1, except that:

[0159] In step (2), no zinc salt is added.

[0160] Comparative Example 3

[0161] The conductive agent, positive electrode sheet, negative electrode sheet, separator, electrolyte and secondary battery provided in this comparative example are basically the same as those in Example 1, except that:

[0162] Conductive agent:

[0163] (1) Weigh 20 g of trisodium citrate dihydrate and place it in a tube furnace. Heat the mixture at 5 °C / min with argon flowing throughout the process. -1 The sample was heated at 800 °C for 3 h at a heating rate, ground once for 10 min after cooling, pickled with 1 M H2SO4, washed with ethanol and deionized water in a filtration device, and vacuum dried at 60 °C for 12 h. Finally, the sample was manually ground clockwise for 45 min using an agate mortar to obtain carbon nanosheets.

[0164] (2) 0.5 g of carbon nanosheets, 1.5 g of D-(+)-glucosamine hydrochloride and 2.23 g of zinc nitrate were stirred in 150 mL of deionized water for 1 h, then reacted in a water bath at 120° C. for 24 h and centrifuged to obtain a conductive agent.

[0165] Among them, the mass ratio of carbon nanosheets to zinc salt is 1:4.46.

[0166] Comparative Example 4

[0167] Conductive agent: Commercially available SP conductive agent (manufacturer: Yiruishi Graphite and Carbon Company).

[0168] Positive electrode:

[0169] The positive electrode active material lithium iron phosphate (LiFePO4), the binder polyvinylidene fluoride (PVDF) and the conductive agent carbon black (SP) are mixed in a mass ratio of 97.2:2:0.8, and N-methylpyrrolidone is added to prepare a positive electrode slurry; the positive electrode slurry is evenly coated on an aluminum foil, dried, cold pressed, and cut to obtain a positive electrode sheet.

[0170] Negative plate:

[0171] The negative electrode active material artificial graphite, the adhesive styrene butadiene rubber (SBR), the auxiliary agent carboxymethyl cellulose (CMC) and the above-mentioned conductive agent are mixed in a mass ratio of 96.5:1.5:1.2:0.8, and deionized water is added to prepare a negative electrode slurry; the negative electrode slurry is evenly coated on a copper foil, and after drying, it is cold pressed and cut to obtain a negative electrode sheet.

[0172] Diaphragm:

[0173] The polyethylene (PE) separator is 9 μm thick and PVDF with a thickness of 1 μm is dot-coated on both sides.

[0174] Electrolyte:

[0175] 10 wt % of lithium hexafluorophosphate (LiPF6), 1 wt % of vinylene carbonate and 2 wt % of vinyl sulfate (DTD) were added to a mixed solvent of ethylene carbonate (EC): ethyl methyl carbonate (EMC): diethyl carbonate (DEC) = 3:5:2 as lithium salt and additives respectively to prepare an electrolyte.

[0176] Secondary battery:

[0177] The positive electrode sheet, separator and negative electrode sheet are stacked in order, and then wound into a square bare battery cell, filled with aluminum-plastic film, injected with electrolyte and sealed. After static formation, capacity division and other processes, a secondary battery is obtained.

[0178] Test Case

[0179] (1) Product parameters of conductive agent

[0180] The parameters of the conductive agents prepared in the above examples and comparative examples are shown in Table 1. The average thickness of the single layer is measured by scanning electron microscopy; the specific surface area and porosity are measured according to the gas adsorption BET method of GB / T 19587-2004; and the single layer conductivity is measured according to ASTM F76-08.

[0181] (2) High temperature cycle performance test

[0182] Place the battery in a 45℃ oven and let it stand for 2 hours. When the battery temperature is maintained at 45℃, perform the charge and discharge test. Charge at 1C constant current to 3.65V, continue constant voltage charging until the charging current is less than 0.05C, then cut off; pause for 5 minutes; discharge at 1C constant current to 2.5V; pause for 5 minutes. The above is a charge and discharge cycle of the battery, which is repeated continuously until the battery capacity decays to 80% of the initial value, and the number of cycles is recorded. The test results are shown in Table 1.

[0183] Table 1

[0184]

[0185] In the table: “ / ” indicates that it cannot be measured or does not have a lamellar structure or a porous structure.

[0186] As shown in Table 1, compared with Examples 1 to 9 and Comparative Examples 1 to 4, the conductive agent provided by the present application, the nitrogen-doped porous carbon nanosheet has a lower average monolayer thickness and a higher specific surface area and porosity, and has good conductivity, which improves the cycle performance of the battery. Therefore, the conductive agent provided by the present application provides a solution for replacing the expensive graphene conductive agent.

[0187] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0188] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the technical concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

Claims

1. A conductive agent, characterized in that: include: Nitrogen-doped porous carbon nanosheets with a layered structure.

2. The conductive agent according to claim 1, characterized in that The pores of the nitrogen-doped porous carbon nanosheets include one or more of spherical pores and cylindrical pores.

3. The conductive agent according to claim 1 or 2, characterized in that: The nitrogen-doped porous carbon nanosheets meet one or more of the following conditions: (1) The average thickness of a single layer of the nitrogen-doped porous carbon nanosheet is 5 nm to 50 nm; (2) The specific surface area of ​​the nitrogen-doped porous carbon nanosheet is 100 m 2 / g~150m 2 / g; (3) The porosity of the nitrogen-doped porous carbon nanosheet is 70% to 85%; (4) The single-layer electrical conductivity of the nitrogen-doped porous carbon nanosheet is 90 S / cm to 110 S / cm.

4. A method for preparing a conductive agent, characterized in that: The following steps are involved: The carbon nanosheets, nitrogen source and zinc salt are added into a solvent for hydrothermal reaction, centrifugally dried and calcined after the reaction, and acid washed after cooling to obtain a conductive agent; Wherein, the conductive agent comprises nitrogen-doped porous carbon nanosheets, and the nitrogen-doped porous carbon nanosheets have a sheet structure.

5. The method for preparing a conductive agent according to claim 4, characterized in that: The maximum value of the calcination temperature is ≥1000°C.

6. The method for preparing a conductive agent according to claim 4, characterized in that: The mass ratio of the carbon nanosheets to the zinc salt is 1:(4-8).

7. A pole piece, characterized in that: include: current collector; as well as An active material layer is disposed on at least a portion of the surface of the current collector, wherein the active material layer comprises an active material and a conductive agent, wherein the conductive agent comprises the conductive agent described in any one of claims 1 to 3 or the conductive agent prepared by the preparation method described in any one of claims 4 to 6.

8. The pole piece according to claim 7, characterized in that: The mass percentage of the conductive agent in the active material layer is 0.6% to 1%.

9. A secondary battery, characterized in that: Comprising a pole piece as claimed in claim 7 or 8.

10. An electrical device, characterized in that: Comprising the secondary battery as claimed in claim 9.